A política eleitoral e judiciária na construção do Estado Imperial. Minas Gerais. (Mariana, 1828-1848) - Joelma Aparecida do Nascimento (2015)
In this thesis, we analyze the performance of justices of the peace in the municipality of Mariana, in the province of Minas Gerais. These figured judges as legally instituted authorities and considered in the legislative Imperial State policies. Laws concerning its functions embraced the electoral system and the judiciary. To link the validity of the laws and their practical application via performance of the judges, split the text into two parts: Part 1 - The electoral system and the justice of the peace, and Part 2 - The judicial system and the justice of the peace. These two parts are composed of five chapters whose main ideas are supported in the critical reflection of historical sources. In the first part we detail the electoral legislation and examine the input and the resourcefulness of the justices of the peace within the municipal elections between the years 1829 and 1848. In Part 2, we emphasize points of the political debate on the judiciary organization and the wide jurisdiction criminal attributed to the judges; Draw your performance in charge of the criminal process between the years 1830 e1839, and study their supervision of the reconciliation of the parties in dispute between 1830 and 1849. Finally, the study brings out the duality that permeates the action of the divided central government on the one hand, the state policy and on the other, by local political practices. We seek to point out that the analysis of the performance of justices of the peace in the municipality of Mariana aligns with the historiographical debate that highlights the roots of a localist political heritage in the organization of the state apparatus. In the 1830s and 1840s, it was confirmed at least with regard to the solid tradition of supporting immersed judicial authorities in the electoral process.